2009
DOI: 10.1016/j.jpdc.2008.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Interconnection of distributed memory models

Abstract: a b s t r a c tIn this paper, we present a framework to formally describe and study the interconnection of distributed shared memory systems. Using it allows us to classify the consistency models in two groups, depending on whether they are fast or not. In the case of non-fast consistency models, we show that they cannot be interconnected in any way. In contrast, in the case of fast consistency models we provide protocols to interconnect some of them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Comprehensive reviews of shared memory consistency models can be found in [26], [10], [7]. Among the consistency models, sequential consistency is most simple and intuitive model that naturally extends the memory behavior of uniprocessor system to multiprocessors systems.…”
Section: System Model and Problem Statementmentioning
confidence: 99%
“…Comprehensive reviews of shared memory consistency models can be found in [26], [10], [7]. Among the consistency models, sequential consistency is most simple and intuitive model that naturally extends the memory behavior of uniprocessor system to multiprocessors systems.…”
Section: System Model and Problem Statementmentioning
confidence: 99%